The Two Powers : the Papacy, the Empire, and the Struggle for Sovereignty in the Thirteenth Century. - Whalen, Brett Edward (Middle Ages Ser., 2019)
Covering decades that included the last major crusades, the birth of the Inquisition, and the unexpected invasion of the Mongols, The Two Powers shows how Popes Gregory and Innocent's battles with Emperor Frederick shaped the political circumstances of the thirteenth-century papacy and its role in the public life of medieval Christendom.